(untitled) (Journal of Advanced Research in Social Sciences, 2020)
Educational researchers incessantly endeavor to address underlying reasons for academic success/failure, and Degree Commitment constitutes a critical sought-after academic outcome regarding college students, which is considerably associated with higher student retention rates. Educational institutions may create effective preventive strategies and interventions for minimizing attrition issues by identifying factors leading to higher Degree Commitment. The aim of the current research was to explore the potential predictive relationship between higher demonstration of college students’ Academic Self-Concept and higher levels of Critical Thinking Dispositions on their commitment of further pursuing their chosen degree. A questionnaire-based survey method was employed, adopting a correlational design on a recruited purposive sample of 120 Greek college students of a privately-owned educational institution. A multiple regression statistical analysis generated a weak positive correlation (9.2%) between the predictors, with Academic Self-Concept being the strongest predictor of Degree Commitment, implying that the combination of the aforementioned academic facets significantly predicts Degree Commitment, but with a small generalization explanatory power to a population sharing common characteristics with the utilized sample. Although the devised model is of minimal practical use, it proposes an initial attempt to construct a holistic model of academic success, while simultaneously highlighting the necessity for developing interventions that robustly target Critical Thinking Dispositions and, most importantly, Academic Self-Concept. Future research may explore factors influencing the predictors under investigation, compare them between students deriving from traditional educational systems and those deriving from international educational systems, and explore alternative factors concerning college success and attrition within various sociocultural contexts.